Dinâmica do crescimento de azevém anual submetido a diferentes intensidades de pastejo - Confortin, Anna Carolina Cerato (2009)
Growth dynamics of Italian ryegrass (Lolium multiflorum Lam) under different grazing intensities were studied, using marked tillers. The experimental design was completely randomized, with four repetitions (transects) and three treatments consisting of grazing intensities: High , Mean and Low , corresponding to the disappearance of 61.0, 43.3 and 21.1% of the initial forage mass value, respectively. The experimental animals were ewe lambs; rotational grazing was used and the thermal sum of 313 degree-days determined the interval among grazing periods. Grazing intensities affected the morphogenesis and structure of Italian ryegrass only in the period from 24/07 to 02/09. During this period, the Italian ryegrass in the Mean grazing intensity had the lowest leaf appearance rate and leaf elongation rate and it had the highest values of leaf life span. The pseudostem height, the length of the intact and defoliated blades, the number of intact and senescent leaves were higher in Low intensity, and did not differ between Mean and High . In Low intensity, the highest growth and senescence flows were registered, respectively, 85.6 and 54.6 kg/ha day of dry matter (DM). In Mean and High intensities, the growth and intake flows were higher in the beginning of pasture utilization and the senescence flow increased during the Italian ryegrass growing season. The choice of the grazing intensity should be based on the aim of management: when the intention is to prioritize individual weight gain, it is recommended the adoption of the intensity of 43.3%, which allows greater intake of blade s leaf by lambs; but when the objective is to prioritize production per area, it is recommended to use the grazing intensity of 61.0%, because under this intensity Italian ryegrass allows higher stocking rate values.